The Grim Reality of War and Love in Hemingway’s A Farewell to Arms and Antoon’s The Corpse washer - Hayfaa A. Ahmed /* Ansam Riyadh Abdullah Almaaroof /*Rouwaida Jasim Mohammed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The theme of love is woven with the theme of War. This study stands on the similarities of themes of War and love in Hemingway’s A farewell to Arms and Sinan Antoon’s The Corpse washer, where War darkened the vision of people. This study gives a short biography of both writers and a summary of both works. Then it discusses the elements and aspects of the two novels to explore the similarities between them by asserting War’s role in restraining the sensitiveness and psychology of the characters who suffer from war in keeping on their love and living. It shows the link between wars despite times and places, the rage that anyone cannot escape physically, psychologically or both. It follows the formalistic as well as the comparative approach in analyzing the selected text. It starts with an introduction, then the discussion occurs, and it ends with a conclusion to show the findings.